Nano patterning of AISI 316L stainless steel with Nonlinear Laser Lithography: Sliding under dry and oil-lubricated conditions. (July 2016) - Gnilitskyi, Iaroslav; Rotundo, Fabio; Martini, Carla; Pavlov, Ihor; Ilday, Serim; Vovk, Evgeny; Ilday, Fatih Ömer; Orazi, Leonardo
Abstract: Femtosecond laser-based Nonlinear Laser Lithography (NLL) was applied to AISI 316L stainless steel, which requires surface modification to achieve satisfactory tribological behaviour. NLL advances over the well-known Laser Induced Periodic Surface Structures (LIPSS) in terms of uniformity and long-range order of high speeds, over large areas. A galvanometric scanner head was used for an high production rate. Dry and lubricated sliding tests, considering different orientations of the nanotexture showed that COF values after NLL treatment are significantly lower. In lubricated tests, COF values of NLL-treated surfaces are nearly half the values of untreated surfaces, whereas the difference further increases when measured in dry conditions, where the orientation of the surface texturing influences the results. Abstract : Graphical abstract: Abstract : Highlights: The surface of AISI 316 was nanostructured by means of Nonlinear Laser Lithography. Different orientations of the quasi-regular linear nanopattern were generated. The morphology and the chemical changes on the surface were investigated. The correlation between the tribologic behaviour and the nanotextures was outlined.